Mutual coupling modeling in transmission lines directly in the phase domain - Silva, R. C. [UNESP]; Costa, E. C M; Kurokawa, S. [UNESP]; Pissolato, J. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper describes a computational model based on lumped elements for the mutual coupling between phases in three-phase transmission lines without the explicit use of modal transformation matrices. The self and mutual parameters and the coupling between phases are modeled using modal transformation techniques. The modal representation is developed from the intrinsic consideration of the modal transformation matrix and the resulting system of time-domain differential equations is described as state equations. Thus, a detailed profile of the currents and the voltages through the line can be easily calculated using numerical or analytical integration methods. However, the original contribution of the article is the proposal of a time-domain model without the successive phase/mode transformations and a practical implementation based on conventional electrical circuits, without the use of electromagnetic theory to model the coupling between phases. © 2011 IEEE.
Keywords: lumped elements; Mutual coupling; state equations; transmission line theory; Analytical integration; Computational model; Electrical circuit; Electromagnetic theories; Lumped element; Modal representation; Modal transformation; Phase domain; Practical implementation; State equations; Time domain; Time-domain model; Transmission line; Differential equations; Electric fields; Electric lines; Equations of state; Numerical methods; Time domain analysis; Transmission line theory; Linear transformations